Analysis of the Lexical Meaning of Harf Jar in Surah Al-Ahqaf - Misbahuddin; Isnaini, Rohmatun Lukluk; Hidayat, Muhammad Rihan (Universitas Yudharta Pasuruan, 2023)
This study aims to analyze the lexical meaning of the harf jar in Surah Al-Ahqaf. The research method used is library research by collecting data through the study of relevant books, literature, notes, and reports. Data analysis is done through the process of data reduction, data presentation, and data verification to conclude the research results. The results showed that there are 70 lexical meanings of 8 types of harf jar in surah Al-Ahqaf. The harf jar "min" has a lexical meaning of "from" with the number of occurrences 17 times. The jar "ilā" has the lexical meaning of "to, to" with the number of occurrences 6 times. The jar "'an" has the lexical meaning of "from, away from" with 3 occurrences. The jar "alā" has the lexical meaning of "above" with 7 occurrences. The jar "fī" has the lexical meaning of "at, in" with 8 occurrences. The harf jar "ba" has the lexical meaning of "with" with 17 occurrences. The jar "kaf" has the lexical meaning of "like, like" with 2 occurrences. The harf jar "lam" has the lexical meaning of "ownership, share" with 10 occurrences.